CURRENT PROBLEMS OF THE SCIENCE OF LAW: A CIVILIST’S VIEW. REVIEW OF THE MONOGRAPH OF V. F. POPONDOPULO “HUMAN ACTIVITY: LEGAL FORMS OF IMPLEMENTATION AND PUBLIC ORGANIZATION” (M.: PROSPECT, 2021. 736 P.) - N. V. Razuvaev (Теоретическая и прикладная юриспруденция)
The article provides a detailed analysis of the monograph V. F. Popondopulo “Human activity: legal forms of implementation and a public organization”. The review author notes the relevance of the monograph, its integrated and comprehensive nature, allowing to deeply explore the phenomenon of human activity as the basis of law enforcement. According to the author, the concept developed by V. F. Popondopulo has a high scientiﬁc and practical value, since it lays the foundation of the theory of law that promotes the crisis of the theoretical and methodological foundations of sectoral legal sciences, primarily the science of civil law. Even though in the monograph V. F. Popondopulo present certain discussion provisions, they, according to the author, not only do not reduce the values of the study, but also stimulate an in-depth study of the problems considered in the study.